Manajemen Dakwah Digital pada Channel YouTube Ustadz Hanan Attaki dalam Membangun Citra Da’i Milenial - Randi Tamirano (IKHBAR: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
The development of digital media has encouraged the transformation of Islamic da'wah from a conventional pattern to a digital platform-based da'wah, one of which is through YouTube. This transformation requires planned and professional da'wah management so that da'wah messages remain effective and able to build a positive image of da'i in the digital public space. This study aims to analyze the management of digital da'wah on Ustadz Hanan Attaki's YouTube Channel in building the image of millennial da'i. This research uses a qualitative approach with a literature study design, with data sources in the form of scientific books, accredited national journal articles, and digital documentation relevant to da'wah and digital da'wah management. The results of the study show that the management of digital da'wah on the Ustadz Hanan Attaki YouTube Channel applies da'wah management functions, including contextual da'wah theme planning, consistent content organization, implementation of da'wah with a polite and persuasive communication style, and evaluation through audience response. The implementation of digital da'wah management contributes to building the image of Ustadz Hanan Attaki as a millennial da'i who is moderate, credible, and relevant to the needs of the younger generation in the digital space.